Drone Radiation Detection System Information Mapping Design Using Quantum Geographic Information System - Dewi, Devina Chandra; Suryaningsih, Fitri (Universitas Muhammadiyah Yogyakarta, 2024)
Scan systems using unmanned aircraft or drone are designed to be able predicted when there is radiation exposure from radioactive sources. The drone is equipped with a Geiger Muller detector type J305 tube and a GPS (Global Positioning System) Tracker and other communication tools. Testing of this system was carried out in the field of B.J. Habibie Serpong, National Research and Innovation Agency using a radioactive source of Cs-137. The drone's flight direction has been designed at the Red Waypoint and has a height of 2 meters. Radiation detection mapping was carried out using Quantum GIS (Geographic Information System) software. The classification parameter in Quantum GIS is divided into 3 parts, namely the first class value is 0.00 to 0.10, the second class is 0.11 to 0.20, and the third class is 0.21 to 0.40. In this study, there are 5 coordinates of the highest radiation value with a red round symbol. These points indicate radiation levels of 0.24, 0.24, 0.24, 0.36, and 0.28. Using identification feature, the mapping results can help the user in analyzing and enable quickly find areas with high radiation. Thus, the decontamination or transfer of radioactive sources can be used as a quick and appropriate follow-up.